PENGEMBANGAN APLIKASI WEB UNTUK MANAJEMEN LAYANAN KESEHATAN (E-HEALTH SYSTEM): SEBUAH TINJAUAN SISTEMATIS LITERATUR - Syakila Yogia Ananda; Cici Aprinda; Mia Ramadani; Awaluddin Awaluddin; Said Al Khudri; Dayanti Dayanti (Jurnal Teknologi dan Bisnis Cerdas, 2026)
The rapid development of digital health technology has encouraged the adoption of web- based applications to improve the accessibility, efficiency, and quality of healthcare services. This study presents a Systematic Literature Review (SLR) on the development of Web-Based Applications for Health Service Management (E-Health System) published between 2020 and 2025. A total of 20 empirical and review studies were selected from reputable databases using the PRISMA 2020 framework. The review identifies five dominant thematic findings: (1) increasing use of telemedicine and patient portals during and after the COVID-19 pandemic;  (2)  the importance of usability and  e-health  literacy for user adoption;  (3) interoperability and integration challenges with Electronic Health Records (EHR); (4) data security, privacy protection, and trust issues; and (5) implementation barriers in low- and middle-income countries, including infrastructure and regulatory limitations. The findings indicate that web-based e-health applications provide significant potential to enhance healthcare delivery performance, yet their successful implementation requires user-centered design, standardized interoperability, robust information security, and supportive public policies. This study contributes to future research by highlighting critical development factors and offering recommendations for more inclusive, secure, and sustainable e-health implementation.